CLASSIFICATION OF ORBITAL DEFORMITIES DUE TO SEQUELAE OF MAXILLOFACIAL TRAUMA (Vietnam Journal of Community Medicine, 2026)
Objective: To classify orbital deformities due to sequelae of maxillofacial trauma.Methods: A descriptive cross-sectional study with analysis, combining retrospective and prospective components, was conducted in patients diagnosed with orbital deformities due to post-traumatic sequelae at Military Central Hospital 108 from September 2018 to August 2019.Results: The study included 35 patients, with a mean interval since trauma of 5 years; 82.9% had previously undergone surgery after trauma. Regarding the classification of orbital deformities, the most common deformed bony rim was the inferior orbital rim (85.7%); the most common deformed bony wall was the inferior wall (77.1%); the most common deformed orbital quadrant was the inferomedial quarter (65.7%); grade 3 enophthalmos was the most frequent degree of enophthalmos (73.3%); and the most common orbital deformity-related manifestations were ocular asymmetry (48.6%), hypoglobus (40%), and ptosis/eyelid drooping (34.3%).Conclusion: Post-traumatic orbital deformities most commonly involve the inferior orbital rim, inferior wall, and inferomedial quarter of the orbit. Grade 3 enophthalmos predominates among orbital deformities.
Keywords: orbital deformity, post-traumatic sequelae.